2021
DOI: 10.51544/jmm.v6i1.2116
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Persepsi Harga Terhadap Minat Beli Smartphone Oppo

Abstract: This study aims to analyze the effect of price perception on Oppo smartphone buying interest in the community of Sukamulia Village Dusun II, Pagar Merbau District. This research uses a quantitative descriptive approach. With a population of 1,174 respondents with a tolerance limit of 10% which is calculated by the Slovin formula, a total sample of 92 respondents was obtained with a sampling technique using random sampling techniques. Data collection was carried out by giving a list of statements to respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of this study support previous research conducted by (Retnowulan, 2017), (Setyarko, 2018), (Satria, 2018), (Hasibuan & Siregar, 2021) where the results of their research are price perceptions have a positive and significant effect on purchase intention. So it can be concluded that the results of this study support the results of previous research.…”
Section: Relationship Between Price Perception and Consumer Purchase ...supporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study support previous research conducted by (Retnowulan, 2017), (Setyarko, 2018), (Satria, 2018), (Hasibuan & Siregar, 2021) where the results of their research are price perceptions have a positive and significant effect on purchase intention. So it can be concluded that the results of this study support the results of previous research.…”
Section: Relationship Between Price Perception and Consumer Purchase ...supporting
confidence: 90%
“…Higher prices are generally associated with higher quality, while lower prices may imply lower quality. Research findings from (Retnowulan, 2017), (Setyarko, 2018), (Satria, 2018), (Hasibuan & Siregar, 2021) consistently demonstrate a positive and significant effect of price perception on consumer buying interest.…”
Section: Price Perception and Consumer Purchase Interestmentioning
confidence: 89%
“…An advertising message is said to be successful, that is, if consumers believe in the product through the advertising message or advertising information they receive (Effendi, 2021). The advertising message presented is accompanied by real evidence of the benefits and quality of the product so it creates trust in the product (Pohan & Sukmal, 2020). Everyone who makes advertisements will usually be made in such a way that consumers can find out information about the product being promoted.…”
mentioning
confidence: 99%